2002
DOI: 10.1159/000065694
|View full text |Cite
|
Sign up to set email alerts
|

Apoferritin Attenuates Experimental Allergic Encephalomyelitis in SJL Mice

Abstract: Ferritin has been shown to attenuate iron-catalyzed oxidative damage in several experimental conditions. Since oxidative damage has been implicated in the pathogenesis of multiple sclerosis (MS) and experimental allergic encephalomyelitis (EAE), an animal model of MS, we tested the hypothesis that ferritin would act to attenuate disease. The experimental design was to increase plasma ferritin levels during the active stage of EAE by giving systemic injections of apoferritin and then compare disease activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Thus, to test this possibility, apoferritin was administered to SJL mice with EAE. Apoferritin was found to suppress disease activity in EAE mice, while injections of iron, which increased serum ferritin levels, failed to ameliorate the disease course 117. It was suggested that the ferritin synthesized in response to iron injections quickly acquired the injected iron and lost some or most of its therapeutic potential since ferritin loaded with iron can release iron, especially when exposed to superoxide anion radical or nitric oxide 118,119.…”
Section: Therapeutic Approaches Targeting Pathogenic Mechanism Involvmentioning
confidence: 99%
“…Thus, to test this possibility, apoferritin was administered to SJL mice with EAE. Apoferritin was found to suppress disease activity in EAE mice, while injections of iron, which increased serum ferritin levels, failed to ameliorate the disease course 117. It was suggested that the ferritin synthesized in response to iron injections quickly acquired the injected iron and lost some or most of its therapeutic potential since ferritin loaded with iron can release iron, especially when exposed to superoxide anion radical or nitric oxide 118,119.…”
Section: Therapeutic Approaches Targeting Pathogenic Mechanism Involvmentioning
confidence: 99%
“…Apoferritin can bind large amounts of iron and protect against oxidative injury (discussed in LeVine et al, 2002). When it was administered during active disease (750 Όg, twice daily), apoferritin lessened clinical signs of EAE in SJL female mice given PLP peptide as an encephalitogen and pertussis toxin injections (LeVine et al, 2002) (Table 1).…”
Section: Iron Chelation In Eaementioning
confidence: 99%
“…When it was administered during active disease (750 Όg, twice daily), apoferritin lessened clinical signs of EAE in SJL female mice given PLP peptide as an encephalitogen and pertussis toxin injections (LeVine et al, 2002) (Table 1). …”
Section: Iron Chelation In Eaementioning
confidence: 99%
“…48 Reactive Oxygen Species participate in the pathogenesis of allergic encephalomyelitis, whereas the infusion of apoferritin in experimental animals may induce a remission status. 49 Thyroid hormone upregulates ferritin genes' expression, and elevated serum ferritin levels have been reported in patients with subacute thyroiditis, which were correlated with disease activity. These levels were higher, as compared to patients with Graves' disease and Hashimoto's thyroiditis.…”
Section: The Role Of Iron In Inflammatory and Neoplastic Diseasesmentioning
confidence: 99%